Correction of Massive Bleedings in Severe Forms of Gestosis - S. V. Tumanyan; D. V. Sidko; R. F. Surovtsev (Общая реаниматология, 2005)
The authors analyzed the efficiency of different variants of infusion-transfusion therapy (ITT) programs in 47 patients with severe gestosis in whom pregnancy or labor was complicated by massive or supermassive blood loss. The use of hyperosmolar solution in combination with natural and artificial colloids in the ITT programs could reduce interstitial hyperhydration. That of erythrocyte-containing components in combination with perfluorane permitted maintenance of tissue oxygen supply even in supermassive blood loss. Addition of reamberin and neoton to infusion media could maintain inotropic myocardial function and provided antiis-chemic protection, contributing to the prevention of multiple organ dysfunction and to the reduction of maternal mortality.